163k views
5 votes
Use the Remainder Theorem to find the remainder when f(x) = x^4 + 4x^3 - x^2 - 16x -12 is divided by x - 4.

36
420
548
-92

User Fulatoro
by
5.8k points

1 Answer

3 votes

Answer:

420

Explanation:

The remainder theorem tells you the remainder is f(4), which you can find by evaluating the expression for x=4. Evaluation is simpler if the expression is written in Horner form first.

... f(x) = (((x +4)x -1)x -16)x -12

... f(4) = (((4 +4)4 -1)4 -16)4 -12

... = ((8·4 -1)4 -16)4 -12

... = (31·4 -16)4 -12

... = 108·4 -12 = 420

_____

Comment on evauation using Horner's form

The intermediate results (contents of parentheses) are the same as the intermediate results you get when you use synthetic division.

Use the Remainder Theorem to find the remainder when f(x) = x^4 + 4x^3 - x^2 - 16x-example-1
User Catrice
by
5.8k points